A new brachylophosaurin (Dinosauria: Hadrosauridae) from the Upper Cretaceous Menefee Formation of New Mexico - Andrew T. McDonald; Douglas G. Wolfe; Elizabeth A. Freedman Fowler; Terry A. Gates (PeerJ, 2021)
Brachylophosaurini is a clade of hadrosaurid dinosaurs from the Campanian of western North America. Although well-known from northern localities in Montana and Alberta, including abundant material of Brachylophosaurus canadensis and Maiasaura peeblesorum and the holotypes of Acristavus gagslarsoni and Probrachylophosaurus bergei, material from southern localities in Utah and Colorado is restricted to a partial skull referred to A. gagslarsoni and several indeterminate specimens. Here we describe Ornatops incantatus gen. et sp. nov., a new brachylophosaurin known from a partial skeleton from the Allison Member of the Menefee Formation in New Mexico. Ornatops is the first brachylophosaurin reported from New Mexico and the southernmost occurrence of the clade. Ornatops shares with Probrachylophosaurus and Brachylophosaurus a caudally expanded nasofrontal suture on the frontals, but also exhibits an autapomorphic nasofrontal suture morphology, with a horizontal rostral region and elevated caudal region with two prominent parasagittal bumps, which is different from other brachylophosaurin specimens, including juvenile and adult Brachylophosaurus. A phylogenetic analysis places Ornatops in a trichotomy with Probrachylophosaurus and Brachylophosaurus, with Maiasaura and Acristavus as successive outgroups.